Consolidated plan of assistance 2012-2014 - United Nations Development Programme (Jerusalem United Nations Development Programme (UNDP))
UNDP/PAPP's Development for Freedom: Empowered Lives. Resilient Nation:
2012 - 2014 places the
Palestinian People at the centre of development programming geared to support their aspiration for Statehood.
It focuses particularly on three geographic areas where the needs and the challenges are the greatest in
achieving sustainable human development and statehood: the Gaza Strip, East Jerusalem and Area C.
The Gaza Strip has been deprived of development since the imposition by Israel of a comprehensive
blockade in 2007. As a result, development and reconstruction needs in the Strip are enormous: from
governance and livelihoods to environment and infrastructure, especially in the aftermath of the military
Operation Cast Lead (December 2008-January 2009). Unemployment rates in Gaza remain amongst the
highest in the world, all while some 80 percent of the population receive humanitarian
assistance in the absence of socio-economic development.
In East Jerusalem, Palestinians face restrictive construction policies and, as a result, experience a growing
housing and property crisis. The erection of the Separation Wall has undermined the economy of East
Jerusalem and is a main cause of growing unemployment rates. Basic services and access to land are
unequally distributed by the Jerusalem municipality and are insufficient to cater to Palestinians' natural
development needs, including housing, education and health.
Development in Area C too is subjected to restrictive policies and practices, hampering any socio-economic
development or access to natural resources for the Palestinians. Area C is, however, pivotal for the realization
of a Palestinian State. It constitutes 62 percent of the West Bank and contains the bulk of Palestinian
agricultural and grazing land, water sources and underground reservoirs. It is also the only space available for
the expansion of Palestinian population centres and infrastructure, and thus forms the backbone of territorial
contiguity in the West Bank.
In strengthening its focus on particularly affected geographic areas and vulnerable populations (Gaza, East
Jerusalem and Area C), UNDP/PAPP's three-year programme takes its inspiration and guidance from the
Palestinian National Development Plan 2011 - 2013: Establishing the State, Building our Future. To this end,
the substantive focus of this consolidated plan builds on UNDP/PAPP's comparative advantage and added
value in the sectors of Governance, Poverty Reduction, Environment and Infrastructure.
In the Governance sector (Section A - Democratic Governance and the Social Contract), emphasis is
placed on the rule of law, access to justice, local governance and public administration. In addition, attention
is given to the reconciliation process and the need for a strong social contract between the State and its
citizens, including the large and growing youth population.
7
In the Productive Livelihoods sector (Section B - Promoting Productivity and Dignity through Livelihoods),
investments are made in building the resilience of vulnerable Palestinian households. By empowering families,
women and youth to graduate from abject poverty, assistance is geared at achieving economic self-reliance.
This is complemented with support to Palestinian private sector development, trade, import and export to
strengthen the economic base of Palestinian statehood.
In the Environment sector (Section C - Natural Resources and Environment), assistance is provided to the
Palestinian Authority to reclaim, manage and protect the environment and natural resources - all essential
for the survival of communities as well as foundational for national development. Support is also provided to
ensure that climate change adaptation responds to the potentially increasing scarcity of natural resources in
the occupied Palestinian territory.
Finally, the Infrastructure sector (Section D. Public and Social Infrastructure), consolidates and expands
past and on-going interventions in five key sectors: Energy, Transportation, Housing, Education and Health.
Through continued investment in infrastructure in these sectors, assistance aims at addressing the growing
challenges faced by Palestinians in accessing basic services and social rights.
These four focus areas - Governance and Rule of Law, Poverty Reduction, Environment and Infrastructure -
lay the ground for sustainable human development, which in turn premises the full spectrum of social,
economic, cultural, civil and political rights. The recognition of the inextricable link between the root-cause
and statehood thus underpins this consolidated plan, Development for Freedom - Empowered Lives.
Resilient Nation: 2012 -2014.
Acronyms
FOREWORD
EXECUTIVE SUMMARY
UNDP/PAPP IN THE OCCUPIED PALESTINIAN TERRITORY
A. Strengthening Democratic Governance and the Social Contract
1. Justification and Challenges - 2. Priorities - 3. Areas of Assistance :
Focus Area 1: Rule of Law and Access to Justice
Focus Area 2: Local Governance and Public Administration
Focus Area 3: Inclusive Dialogue and Social Contract, including youth and women
Focus Area 4: Reconciliation and Social Cohesion
Focus Area 5: International Representation
B. Promoting Productivity and Dignity through Livelihoods
1. Justification and Challenges - 2.Priorities - 3. Areas of Assistance Focus Area
1: Economic Empowerment of Productive Families
Focus Area 2: Land Protection and Development in the West Bank ( with focus on Area C)
Focus Area 3: Private Sector and Economic Development in Gaza
Focus Area 4: Import Substitution and Export Strategies
C. Protecting Natural Resources and the Environment
1. Justification and Challenges - 2. Priorities - 3. Areas of Assistance:
Focus Area 1: Environment Governance
Focus Area 2: Financing Environment
Focus Area 3: Water Supply, Sanitation and Solid Waste Services
Focus Area 4: Climate Change Adaptation
D. Public and Social Infrastructure
1. Justification and Challenges - 2. Priorities -3. Focus of Assistance:
Focus Area 1: Energy Resources
Focus Area 2: Transport and Management Systems
Focus Area 3: Affordable and Adequate Housing
Focus Area 4: Education
Focus Area 5: Public Health Services and a Health System
Focus Area 6: Heritage Conservation
Title on cover q
Keywords: Economic development; ECONOMIC DEVELOPMENT; DEVELOPMENT AID; DEVELOPMENT PLANS; ECONOMIC PLANNING